Photocatalyst carrier and method for producing photocatalyst carrier
By adjusting the pore structure of the ceramic material and the loading of the photocatalyst, the problem of poor deodorization effect of the existing photocatalyst carrier is solved, and efficient organic matter decomposition and deodorization effect is achieved.
Patent Information
- Application Number
- CN202380058767.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-24
- Filing Date
- 2023-07-14
- Publication Date
- 2025-04-01
AI Technical Summary
The existing photocatalyst carriers have limitations in improving the deodorization effect, and it is difficult to make the porosity of ceramic materials significantly higher than 85%, thereby affecting the deodorization effect.
The porous ceramic material is used as the substrate for the photocatalyst carrier. By adjusting the opening porosity of the ceramic material, the pore diameter and the area ratio of the through-holes, the opening pore rate of the ceramic material is ensured to be 35% or more than 75%, the pore diameter is 100 μm or more than 1000 μm, and the photocatalyst with titanium oxide as the main component is uniformly supported in the substrate.
By increasing the porosity of the photocatalyst support and the loading of the photocatalyst, the deodorization effect is significantly enhanced, so that the photocatalyst support can decompose organic matter in the air more efficiently.
Smart Images

Figure CN119744201A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a photocatalyst carrier and a method for manufacturing the photocatalyst carrier. Background Art
[0002] Deodorizing devices that achieve deodorizing effects by decomposing organic matter using photocatalysts such as titanium oxide have been put into practical use. Such deodorizing devices include a photocatalyst carrier formed by carrying a photocatalyst on the surface of a substrate, a light source that emits light to activate the photocatalyst to the photocatalyst carrier, and an airflow generating mechanism that draws in surrounding air and brings it into contact with the photocatalyst. In order to allow air to efficiently contact the photocatalyst, it has been proposed to use a porous ceramic material as a substrate for the photocatalyst carrier (for example, see Patent Document 1).
[0003] When selecting a ceramic material used as a substrate for a photocatalyst carrier, importance is attached to the material composition that determines mechanical properties and the porosity that is an index of surface area and thus contact efficiency with air. Regarding porosity, Patent Document 1 describes the use of a ceramic porous body with a porosity of 85%. Patent Literature
[0004] Patent Document 1: Japanese Patent No. 4610135 Summary of the invention
[0005] In Patent Document 1, the material is made into multiple layers to achieve high porosity as described above while ensuring mechanical strength. There are open pores (continuous pores) and closed pores (independent pores) in the pores, and it is unclear what proportion of pores the porosity in Patent Document 1 represents. However, no matter what the porosity in Patent Document 1 is, it is difficult to make the porosity of the ceramic material significantly higher than the value in Patent Document 1 in consideration of mechanical strength. Therefore, in order to further improve the deodorization effect, a different method needs to be adopted. In view of the above-mentioned actual situation, the subject of the present invention is to provide a photocatalyst carrier with a high deodorization effect.
[0006] A photocatalyst carrier according to one embodiment of the present invention comprises a substantially plate-shaped substrate formed by a porous ceramic material, and a photocatalyst carried on the surface of the substrate and inside the pores, wherein the open porosity of the ceramic material is greater than 35% and less than 75%, and the ceramic material has large pores with a diameter of greater than 100 μm and less than 1000 μm, and small pores with a diameter of less than 10 μm open on the inner wall surface of the large pores.
[0007] In the photocatalyst carrier, the number of the large pores within a range of 1.8 mm×1.8 mm in a cross section of the ceramic material may be 8 or more and 50 or less.
[0008] In the photocatalyst carrier, the substrate may have a plurality of through holes extending in the thickness direction, the diameter of the through holes may be 0.7 mm to 2.0 mm, and the area ratio of the through holes in the substrate may be 20% to 50%.
[0009] In the photocatalyst carrier, the photocatalyst may have titanium oxide as a main component, and the loading amount of the photocatalyst may be 0.04 g / cm 3 Above 0.15g / cm 3 the following.
[0010] Another embodiment of the present invention relates to a method for manufacturing a photocatalyst carrier, which comprises the steps of immersing a substantially plate-shaped substrate formed of a porous ceramic material in a photocatalyst dispersion in which photocatalyst particles are dispersed in a solvent, drying the substrate, and calcining the substrate, wherein the open porosity of the ceramic material is not less than 35% and not more than 75%, and the ceramic material has large pores with a diameter of not less than 100 μm and not more than 1000 μm, and small pores with a diameter of not more than 10 μm are open on the inner wall surface of the large pores.
[0011] According to the present invention, a photocatalyst carrier having a high deodorizing effect can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a schematic perspective view showing a photocatalyst carrier according to one embodiment of the present invention. Figure 2 For display Figure 1 A flow chart of the sequence of the method for manufacturing a photocatalyst support. Figure 3 This is a cross-sectional SEM image of the substrate of Sample 1. Figure 4 This is a cross-sectional SEM image of the substrate of Sample 7. Figure 5 This is a cross-sectional SEM image of the substrate of Sample 8. Figure 6 This is a cross-sectional SEM image of the substrate of Sample 9. DETAILED DESCRIPTION
[0013] Hereinafter, embodiments of the present invention will be described with reference to the drawings. Figure 1 This is a schematic perspective view showing a photocatalyst carrier 1 according to one embodiment of the present invention.
[0014] The photocatalyst carrier 1 includes a substantially plate-shaped substrate formed of a porous ceramic material, and a photocatalyst supported on the surface of the substrate and inside the pores.
[0015] By using porous ceramics or ceramic materials having two types of pores, pores larger than 100 μm and fine pores smaller than 10 μm, as the substrate of the photocatalyst carrier 1, it is possible to perform primary adsorption and retention of organic matter in the air, and utilize the catalytic effect of the photocatalyst to gradually decompose the adsorbed organic matter over time, thereby increasing the deodorization effect.
[0016] The ceramic material forming the substrate preferably has relatively cheap silicon dioxide as the main component, which can improve mechanical properties, and preferably contains cheaper aluminum oxide. Specifically, in order to suppress costs, the lower limit of the combined content of silicon dioxide and aluminum oxide is preferably 60% or more, and more preferably 80%. On the other hand, in order to contain additives that optimize the physical properties of the material, the upper limit of the combined content of silicon dioxide and aluminum oxide is preferably 98%, and more preferably 97%. In addition, in order to improve strength, the lower limit of the ratio of silicon dioxide to aluminum oxide is preferably 1.0, and more preferably 1.2. On the other hand, in order to suppress costs, the upper limit of the ratio of silicon dioxide to aluminum oxide is preferably 3.0, and more preferably 2.5.
[0017] The lower limit of the open porosity of the ceramic material forming the substrate is preferably 35%, more preferably 40%, and further preferably 50%. On the other hand, the upper limit of the open porosity of the ceramic material forming the substrate is preferably 75%, and more preferably 70%. By setting the open porosity of the ceramic material to be above the above lower limit, the amount of photocatalyst carried inside the pores of the substrate can be increased, thereby enhancing the deodorization effect of the photocatalyst carrier 1 (the effect of decomposing organic matter by the catalytic effect of the photocatalyst). In addition, by setting the open porosity of the ceramic material to be below the above upper limit, the mechanical strength of the substrate can be ensured. It should be noted that the "open porosity" is measured according to the boiling method of JIS-R1634 (1998).
[0018] The ceramic material forming the substrate has large pores with a diameter of 100 μm or more and 1000 μm or less, and small pores with a diameter of 10 μm or less. The density distribution of the pore diameter of the ceramic material preferably has a peak of 100 μm or more and 1000 μm or less and a peak of 10 μm or less. In the ceramic material, the small pores are preferably also opened on the inner wall surface of the large pores. When the pore diameter is too large, the specific surface area of the porous ceramic becomes smaller, resulting in a reduction in the adsorption capacity of organic matter and a decrease in the amount of photocatalyst loaded. On the contrary, if the pore diameter becomes too small, the photocatalyst dispersion liquid will not penetrate into the fine part, and the problem of reducing the amount of photocatalyst loaded will occur. Due to the presence of large pores with a pore diameter of 100 or more and 1000 μm or less, the photocatalyst dispersion liquid penetrates into the interior and can efficiently load the photocatalyst. Furthermore, if the doped pores have a diameter of less than 10 μm, the photocatalyst dispersion liquid impregnated into the large pores can easily penetrate into the small pores, so that the photocatalyst can be uniformly loaded in the deep part of the substrate, thereby further improving the deodorization efficiency. From this point of view, the number of large pores is preferably 8 or more to 50 within the range of a square of 1.8 mm × 1.8 mm in the cross section of the porous ceramic. It should be noted that the "pore diameter" is the average value of the major axis and minor axis of each pore in the scanning electron microscope image of the cross section of the ceramic material. In more detail, the ceramic material is processed into a rod with a cross section of about 10 × 10 mm, the rod is cut using a band saw, the surface is coated by an ion sputtering device, and then photographed using a scanning electron microscope. For the scanning electron microscope, an S3400 manufactured by Hitachi HiTech Co., Ltd. was used to take images at 15 kV.
[0019] To ensure strength, the lower limit of the thickness of the substrate is preferably 8 mm, more preferably 10 mm. On the other hand, to allow light to irradiate the photocatalyst inside the pores to activate the catalytic action, the upper limit of the thickness of the substrate is preferably 20 mm, more preferably 15 mm.
[0020] The substrate and the photocatalyst carrier 1 have a plurality of through holes 11 penetrating in the thickness direction. The through holes 11 serve as air flow paths and reduce the pressure loss of the air, thereby suppressing the load of the fan that forms the air flow. By reducing the diameter of the through holes 11, air enters the pores of the substrate on the outside from the inner peripheral surface of the through holes 11, thereby promoting the deodorization effect. Such through holes 11 are preferably formed regularly at equal intervals in substantially the entire photocatalyst carrier 1 except for the outer edge.
[0021] In order to facilitate formation, the lower limit of the diameter of the through hole 11 is preferably 0.7 mm, and more preferably 1.0 mm. On the other hand, in order to prevent air from passing through without contacting the photocatalyst, the upper limit of the diameter of the through hole 11 is preferably 2.0 mm, and more preferably 1.5 mm. In order to sufficiently reduce pressure loss, the lower limit of the area ratio of the through hole 11 in the substrate is preferably 20%, and more preferably 25%. On the other hand, in order to promote contact between air and the photocatalyst, the upper limit of the area ratio of the through hole 11 in the substrate is preferably 50%, and more preferably 40%. It should be noted that "diameter" is an equivalent circle diameter, that is, the diameter of a circle with equal area.
[0022] The photocatalyst preferably contains titanium oxide having excellent photocatalytic effect, more specifically, anatase-type titanium dioxide as the main component. The particle size (median particle size) of the photocatalyst is preferably 50 nm to 400 nm in order to be introduced into the pores of the substrate.
[0023] The photocatalyst is supported almost evenly on the entire substrate. In order to obtain a sufficient deodorizing effect, the lower limit of the amount of photocatalyst supported per volume of the photocatalyst carrier 1 (including the internal space of the through-hole 11) is preferably 0.04 g / cm 3 , more preferably 0.06 g / cm 3 On the other hand, in order to uniformly support the photocatalyst without blocking the pores of the ceramic substrate, the upper limit of the supported amount of the photocatalyst per volume of the photocatalyst carrier 1 is preferably 0.15 g / cm 3 , more preferably 0.10 g / cm 3 .
[0024] The photocatalyst carrier 1 having the above structure can evenly hold the photocatalyst at a relatively high density even inside the photocatalyst, and can effectively decompose organic matter in the air by utilizing the catalytic action of the photocatalyst, thus achieving a high deodorizing effect.
[0025] The photocatalyst carrier 1 is Figure 2 The photocatalyst carrier 1 is manufactured by an embodiment of the method for manufacturing a photocatalyst carrier according to the present invention. The photocatalyst carrier 1 is manufactured by a method comprising a step of forming a substrate (step S1: substrate forming step), a step of immersing the substrate in a photocatalyst dispersion liquid (step S2: immersion step), a step of drying the substrate (step S3: drying step), and a step of calcining the substrate (step S4: calcining step).
[0026] In the substrate forming process of step S1, a substrate having a desired porosity and pore diameter and a desired outer shape is formed. In the substrate forming process, by mixing a powder that decomposes at a ceramic calcining temperature in a known ceramic raw material and forming it, and calcining the formed body, a porous ceramic doped with large pores with a relatively large diameter of more than 100 μm and less than 1000 μm and small pores with a diameter of less than 10 μm as described above that are not seen in general ceramic materials can be formed. As a powder material for forming large pores, substances that decompose at high temperatures, such as wine lees, rice bran, soybean meal, coal, charcoal, and plastics, can be used. The particle size of the powder material that determines the diameter of the large pores can be adjusted by adjusting the mixing conditions of a mixer such as a kneader or an extruder.
[0027] In the impregnation process of step S2, the substrate formed by the porous ceramic material as described above is immersed in a photocatalyst dispersion liquid in which photocatalyst particles are dispersed in a solvent, thereby allowing the photocatalyst dispersion liquid to penetrate the substrate. Since the substrate is formed by a ceramic material having large pores and small pores, the catalyst dispersion liquid will evenly penetrate into the interior of the substrate. As a solvent for the photocatalyst dispersion liquid, for example, 2-propanol, water, etc. can be used. In order to introduce the photocatalyst with sufficient density while ensuring permeability to the interior of the substrate, the photocatalyst concentration in the photocatalyst dispersion liquid is preferably set to more than 10% and less than 40%. The photocatalyst dispersion liquid may also contain an adhesive that promotes the fastening of the photocatalyst particles to the substrate.
[0028] In the drying process of step S3, the substrate impregnated with the photocatalyst dispersion is dried, thereby attaching the photocatalyst particles to the outer surface of the substrate and the inner surface of the pores. Once the solvent of the photocatalyst dispersion is boiled, the photocatalyst particles may be detached, so it is preferred to dry at a temperature sufficiently lower than the boiling point of the solvent. For example, when the solvent of the catalyst dispersion is 2-propanol, drying can be performed at room temperature for 24 hours.
[0029] In the calcination process of step S4, the substrate after the impregnation of the catalyst dispersion is dried is calcined, thereby fastening the photocatalyst particles to the substrate. The calcination conditions can be set, for example, to be heated at 500°C for 1 hour and then gradually cooled to room temperature. Since the substrate has large pores, the photocatalyst after calcination easily forms a continuous layer, so the photocatalyst becomes less likely to fall off from the substrate.
[0030] As described above, by undergoing the impregnation step, the drying step, and the calcination step, the photocatalyst can be uniformly supported even inside the pores of the substrate with relatively small diameters. The photocatalyst carrier 1 manufactured in this way can exhibit the high deodorizing effect as described above.
[0031] As mentioned above, although embodiment of this invention was described, this invention is not limited to the said embodiment, Various changes and deformation|transformation are possible. Example
[0032] Hereinafter, the present invention will be specifically described based on examples, but the present invention is not limited to the following examples.
[0033] Prepare various substrates made of ceramic materials according to Figure 2 Photocatalyst carrier samples 1 to 11 were prepared in the order shown. As the substrate, ceramic materials with different porosity, pore diameter, and through-hole area ratio were prepared. As a representative example showing the difference in pore shape of ceramic materials, Figures 3 to 6 The scanning microscope images of the samples 1, 7, 8, and 9 are shown in FIG. It should be noted that the “total porosity” is the volume ratio of all pores including closed pores, and the “porosity” is the sum of the volume ratio of all pores and the volume ratio of through pores in the material. In addition, the “water absorption rate” is the value measured according to the boiling method of JIS-A1509-3 (2014).
[0034] For the obtained photocatalyst carrier prototype, in order to evaluate the deodorization performance, a test was conducted to decompose ammonia and aldehyde in a closed container, and the time required for decomposition was measured. The following Table 1 shows the composition of the ceramic material, physical properties, geometric information of the substrate, the amount of photocatalyst loaded, and the deodorization performance of each prototype. It should be noted that "-" in the table means no measured value, and "120<" means that the odor component cannot be decomposed within 120 minutes, and the test is over.
[0035] [Table 1]
[0036] As described above, it was confirmed that the deodorizing effect of the photocatalyst carrier can be improved by setting the pore diameter of the substrate within a certain range. Explanation of symbols
[0037] 1 Photocatalyst carrier 11 through holes.
Claims
1. A photocatalyst carrier, comprising: a substantially plate-shaped substrate formed of a porous ceramic material; and a photocatalyst supported on the surface of the substrate and inside the pores, The open porosity of the ceramic material is not less than 35% and not more than 75%, The ceramic material has large pores with a diameter of 100 μm or more and 1000 μm or less. Small pores with a diameter of 10 μm or less open on the inner wall surface of the large pores.
2. The photocatalyst carrier according to claim 1, wherein The number of the large pores within a range of 1.8 mm×1.8 mm in the cross section of the ceramic material is 8 or more and 50 or less.
3. The photocatalyst carrier according to claim 1 or 2, wherein The substrate has a plurality of through holes extending through the substrate in a thickness direction. The diameter of the through hole is not less than 0.7 mm and not more than 2.0 mm. The area ratio of the through holes in the substrate is 20% to 50%.
4. The photocatalyst carrier according to claim 1 or 2, wherein The photocatalyst has titanium oxide as a main component. The photocatalyst loading is 0.04 g / cm 3 Above 0.15g / cm 3 the following.
5. A method for producing a photocatalyst carrier, comprising: A step of immersing a substantially plate-shaped substrate formed of a porous ceramic material in a photocatalyst dispersion liquid in which photocatalyst particles are dispersed in a solvent; a step of drying the substrate; and The step of calcining the substrate, The open porosity of the ceramic material is not less than 35% and not more than 75%, The ceramic material has large pores with a diameter of 100 μm or more and 1000 μm or less. Small pores with a diameter of 10 μm or less open on the inner wall surface of the large pores.
Citation Information
Patent Citations
JP1971010135Y1